2010
DOI: 10.1002/mds.23293
|View full text |Cite
|
Sign up to set email alerts
|

MRI measurements of brainstem structures in patients with Richardson's syndrome, progressive supranuclear palsy-parkinsonism, and Parkinson's disease

Abstract: We investigated the diagnostic accuracy of brainstem MRI measurements in patients with different progressive supranuclear palsy (PSP) syndromes and Parkinson's disease (PD). Using 3D T1-weighted images, midbrain, and pons areas, as well as superior (SCP) and middle cerebellar peduncle (MCP) widths were measured in 10 patients with Richardson's syndrome (PSP-RS), 10 patients with PSP-parkinsonism (PSP-P), 25 patients with PD, and 24 healthy controls. The ratio between pons and midbrain areas (pons/midbrain), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 37 publications
9
101
2
1
Order By: Relevance
“…The similarity of ROI-measured atrophy rates between PSP and PSP-DAV supports the conclusion that the larger PSP-DAV sample size enabled detection of smaller cortical changes using VBM maps, which indicate statistical significance but not magnitude. In addition, the midbrain to pons ratio, which has previously been shown to be decreased in PSP, [26][27][28][29][30] was nearly identical in the PSP and PSP-DAV groups and smaller than in the CBS or NC group. Future studies of autopsy-confirmed CBD and PSP cases will be necessary to definitively determine the differences in rates of volume loss between these disorders.…”
Section: Magnitude Of Longitudinal Volumetric Changes In Definedmentioning
confidence: 56%
See 1 more Smart Citation
“…The similarity of ROI-measured atrophy rates between PSP and PSP-DAV supports the conclusion that the larger PSP-DAV sample size enabled detection of smaller cortical changes using VBM maps, which indicate statistical significance but not magnitude. In addition, the midbrain to pons ratio, which has previously been shown to be decreased in PSP, [26][27][28][29][30] was nearly identical in the PSP and PSP-DAV groups and smaller than in the CBS or NC group. Future studies of autopsy-confirmed CBD and PSP cases will be necessary to definitively determine the differences in rates of volume loss between these disorders.…”
Section: Magnitude Of Longitudinal Volumetric Changes In Definedmentioning
confidence: 56%
“…[26][27][28][29][30] At all time points, both PSP and PSP-DAV groups had lower midbrain to pons ratios than NC and CBS groups (figure e-2). Moreover, midbrain/pons ratios within all groups remained stable over 1 year in all groups.…”
Section: Magnitude Of Longitudinal Volumetric Changes In Definedmentioning
confidence: 96%
“…In the diagnostic workup, magnetic resonance imaging (MRI) signs of PSP include prominent midbrain and pons atrophy, which have been combined in the conventional MR parkinsonism index [5,6]. Volumetric/morphometric MRI studies have shown frontal atrophy in PSP [7,8] and have demonstrated tissue loss in fronto-/mesiotemporal cortices and prefrontal regions in addition to the central midbrain and basal ganglia [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…On this basis, many studies have been conducted to identify the MRI index that would help differentiate PSP-RS and PSP-P from PD [10,11,12,13,15,21,22,23,24]. In particular, a previous study reported that PSP-P shows atrophy of the midbrain and superior cerebellar peduncles, the characteristic MRI findings of PSP [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…The midbrain area was traced around the edges of line 1 and the midbrain tegmentum above it. The pons included the area between the lines along the anterior and posterior margins of the pons and lines 1 and 2 [10,11,12,13]. The length of the M TEGM was measured on an axial T1-weighted image using the method of Sung et al [14].…”
Section: Methodsmentioning
confidence: 99%